Pengaruh Kepemilikan Asing, Kualitas Audit, Dan Effective Tax Rate Terhadap Transfer Pricing - Maria Almeida Nagita Putri (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of foreign ownership, audit quality and effective tax rate on transfer pricing. This study uses a sample of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. The sampling method used purposive sampling with criteria set by the researcher so that a sample of 24 companies was used in this study. Management of data in research using multiple linear regression. The results of this study indicate that foreign share ownership has an effect on transfer pricing, audit quality and effective tax rate have no effect on transfer pricing. The contribution in this study empirically explains the relationship between foreign ownership using the percentage of foreign share ownership, audit quality using a dummy variable by determining a sample of company financial statements that are audited by big four KAP with a value of 1 and non-big four KAP with a value of 0, and the effective tax rate using the expense ratio current tax with pre-tax profit. This research provides information for the government to be able to decide on a policy of strict sanctions in overcoming problems related to tax suppression and stakeholders in the company can monitor the company's transaction activities with related parties in countries with low tax rates. Keywords: Foreign Ownership, Audit Quality, Effective Tax Rate, Transfer pricing